How crop insurance influences agricultural green total factor productivity: Evidence from Chinese farmers. (25th October 2021) - Fang, Lan; Hu, Rong; Mao, Hui; Chen, Shaojian
Abstract: As an effective risk guarantee mechanism, crop insurance can not only disperse agricultural operation risk, but also guide the agricultural green development. Based on Chinese provincial panel data from 2002 to 2015, this paper uses SBM-GML (Global-Malmquist-Luenberger) index model to measure agricultural green total factor productivity and systematically examines the impact of crop insurance on agricultural green total factor productivity as well as its mechanism. This study supplements the determinants of agricultural green total factor productivity. It is found that crop insurance has a significant positive impact on agricultural green total factor productivity. The promotion effect of crop insurance on agricultural green total factor productivity increases with the expanded use of agricultural green technologies such as precision sowing, deep fertilization, subsoiling and no-tillage. Moreover, our results show that the role of crop insurance in promoting agricultural green total factor productivity increases with the increase in operational scales. In addition, compared with food crops, the promotion effect is stronger for cash crops. Therefore, the Chinese government should continue to support the implementation of crop insurance policy. It is necessary to not only increase crop insurance subsidies, but also set up differentiated subsidy systems in different operational scales and planting structures to promote agricultural green development. Highlights: Crop insurance has a significant positive impact on AGTFP. The promotion effect of crop insurance on AGTFP increases with the expanded use of agricultural green technologies. The role of crop insurance in promoting AGTFP increases with the increase in operational scales. Compared with food crops, the promotion of crop insurance on AGTFP is stronger for cash crops.